Impact of Telemedicine Adoption on Patient Satisfaction during Post-Pandemic Healthcare Delivery in Ethiopia - Tadesse, Milo (International Journal of Health Sciences, 2025)
Purpose: The aim of the study was to investigate the impact of telemedicine adoption on patient satisfaction during post-pandemic healthcare delivery. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Telemedicine has improved patient satisfaction by increasing accessibility, reducing travel and wait times, and offering flexible appointments. Patients appreciated the convenience, but challenges like digital literacy gaps, limited internet access, and data privacy concerns affected satisfaction for some. Personalized provider communication significantly boosted positive experiences. Disparities in satisfaction were observed, with older adults and low-income groups facing more barriers. Unique Contribution to Theory, Practice and Policy: Technology acceptance model (TAM), diffusion of innovations theory & expectation-confirmation theory (ECT) may be used to anchor future studies on the impact of telemedicine adoption on patient satisfaction during post-pandemic healthcare delivery. Telemedicine platforms should be developed with a user-centric approach, emphasizing simplicity, accessibility, and adaptability to meet the needs of diverse patient populations, including older adults and those with limited digital skills. Policymakers should also introduce incentives such as subsidies for technology upgrades and reimbursement parity between telemedicine and in-person visits to encourage widespread adoption.